Assessment of Library and Information Professionals’ Perception of COVID-19 and Its Impacts on Libraries in Nigeria - Adegbilero-Iwari, Idowu; Ikenwe, Iguehi Joy; Adegbilero-Iwari, Oluwaseun Eniola (International Journal of Knowledge Content Development & Technology, 2022)
Perceptions of Library and Information (LI) professionals in Nigeria and the impact of COVID-19 on libraries, librarians and library services, were studied. The significance of demographic factors on LI professionals’ perception of COVID-19 and its impact on libraries was tested. Descriptive survey design and Purpose sampling technique were adopted. LIS professionals in Nigeria constituted the population, and an online questionnaire designed by the researchers through Microsoft Forms was used. Descriptive analysis of respondents’ demographic data and their covid-19 perception were presented in frequencies and percentages using tables while multivariate regression technique was used to test the significance of relationship between variables at P < 0.05. Findings revealed that many (61.4%) of the respondents agreed that COVID-19 is real but have personal reservations. However, 47.5% indicated that COVID-19 is a scientific invention. On the impacts of COVID-19 on libraries, the study found that COVID-19 is a game changer that will enhance the creation of new services by libraries, cause the reconfiguration of library space for safe operations in post-COVID, establishment of new rules and regulations, and more reliance on e-resources. On the test of association, educational qualification of respondents had a significant impact on respondents’ perceptions that COVID-19 will reduce the use of library print resources (P-value = 0.005, B: 0.38, [95% CI: 0.115 – 0.646]) and that library will create new services to address the changes caused by COVID-19. Also, educational qualification of respondents significantly influenced respondents’ perception that COVID-19 is real. The study recommends that libraries should take advantage of the season to innovate, and that public health institutions should continually educate people on corona virus to disabuse people’s mind of conspiracy theories.